Governance through development : poverty reduction strategies, international law and the disciplining of third world states - Tan, Celine (Milton Park, Abingdon, Oxon : Routledge, 2011)
'Governance Through Development' locates the Poverty Reduction Strategy Paper framework within the broader context of international law and global governance; exploring its impact on third world state engagement with the global political economy and the international regulatory norms and institutions which support it.
PRSPs in postcolonial international law and global governance -- PRSPs and the crisis of legitimacy in the international order -- Ownership as conditionality : PRSPs and the evolution of conditional financing -- Reforming the nation state : PRSPs and rehabilitating the structurally adjusted state -- Redesigning the political project : discipline and legitimation through participatory policymaking -- Consolidation and conclusion : PRSPs, transnational governance and globalised legal regimes.
Includes bibliographical references and index.
Keywords: Poverty -- Government policy -- Developing countries; Economic assistance -- Developing countries -- Management; Law and economic development